2002
DOI: 10.1155/s016117120201325x
|View full text |Cite
|
Sign up to set email alerts
|

Singularly perturbed Volterra integral equations with weakly singular kernels

Abstract: We consider finding asymptotic solutions of the singularly perturbed linear Volterra integral equations with weakly singular kernels. An interesting aspect of these problems is that the discontinuity of the kernel causes layer solutions to decay algebraically rather than exponentially within the initial (boundary) layer. To analyse this phenomenon, the paper demonstrates the similarity that these solutions have to a special function called the Mittag-Leffler function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…This result agrees with that obtained in [3] for f (x,s) = x using the explicit solution in terms of the Mittag-Leffler function.…”
Section: Properties Of the Formal Solutionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result agrees with that obtained in [3] for f (x,s) = x using the explicit solution in terms of the Mittag-Leffler function.…”
Section: Properties Of the Formal Solutionsupporting
confidence: 91%
“…To date, apart from the present paper, there have been no efforts to prove the validity of the formal approximation to nonlinear singularly perturbed Volterra integral equations with weakly singular kernels. The linear version of (1.1) has been studied in [3], where it is shown that the formal asymptotic solution is the sum of a slowly varying function and a rapidly varying function, described in terms of the Mittag-Leffler function. The Mittag-Leffler function (a special function) is an example of functions which decay algebraically at infinity, as pointed in the previous paragraph.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the case g(0) ≠ 0 is not covered in the analysis presented in [1]. Recently, [2] studied, rigorously, asymptotic solutions of singularly perturbed linear Volterra integral equations with weakly singular kernels using the additive decomposition method. It is shown in [2] that the inner layer solution can explicitly be written in terms of the Mittag-Leffler function which tends to zero algebraically at infinity.…”
mentioning
confidence: 99%
“…Recently, [2] studied, rigorously, asymptotic solutions of singularly perturbed linear Volterra integral equations with weakly singular kernels using the additive decomposition method. It is shown in [2] that the inner layer solution can explicitly be written in terms of the Mittag-Leffler function which tends to zero algebraically at infinity. Adopting the techniques used in [2] here, the formal asymptotic solution for (1.1) is derived by revealing the structure of its contents and proof of asymptotic correctness presented.…”
mentioning
confidence: 99%
See 1 more Smart Citation